Palatal obturator prosthesis: case series - DOMINGUES,Juliana Machado (2016)
ABSTRACT Surgical treatment for palate cancers can result in oral-nasal/sinus communication, which impairs the swallowing, speech and chewing ability of patients with reflux of ingested food into the nasal cavity, reducing their quality of life. This article aims to report how three cancer patients, with different types of palate cancer undergoing partial maxillectomy with oroantral or oral-nasal communication as postoperative sequelae were prosthetically rehabilitated from 2009 to 2015. The prostheses were made by dental-surgeons interns in the service of the Multidisciplinary Residency in Oncological Healthcare of the Hospital School of the Federal University of Pelotas (HE/UFPel). One of the patients is completely edentulous, the second partially toothed and in the third case the patient is totally toothed, only requiring the obturator. The creation of prosthetic rehabilitation followed the steps of conventional prostheses, especially observing the particularities in the planning, molding, installation and adjustment stages of the prosthesis. In all cases there was improvement on speech immediately after the prosthesis installation and patients reported greater ease to feed.